The Impact of Multinational Enterprise Strategy on Indigenous Enterprises: Horizontal Spillovers and Crowding Out in Developing Countries - Spencer, Jennifer W. (Academy of Management Review, 2008)
Under what conditions does a multinational enterprise's (MNE's) investment in a developing country produce spillovers for local firms operating in the same industry? In this paper I view firms as unique configurations of tacit and codified knowledge, and I propose that the strategies pursued by an MNE will determine whether the investment will create positive externalities, through knowledge diffusion and provision of public goods, or negative externalities, through a crowding out effect on indigenous enterprises.